2022
DOI: 10.4102/jomped.v6i1.144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of 40% and 0% shading levels on the secondary metabolites, antifungal and anti-insect activities of extracts of Allium porrum cultivated hydroponically under greenhouse conditions

Abstract: Background: Allium species are generally reputed for their anti-pest properties; however, few studies have focused on optimising the quality and yield of anti-pest bioactive materials from these medicinal plants.Setting: Laboratory and greenhouse experiments were carried out on the Bellville campus of the Cape Peninsula University of Technology, Cape Town.Aims: This research study aimed to evaluate the effect of light intensity on the volatile constituents, antifungal and anti-insect activities of extracts obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…This study found similar results: the TPC contents of 14 species of Indocalamus in different seasons ranged between 1.27 mg•g −1 and 5.41 mg•g −1 . Ntobela [54] demonstrated that low-light environments induced an increase in the contents of volatiles and phenolics, and Formisano [55] found that a low-light environment can promote the accumulation of total phenolic compounds. In this study, after the ST treatment, the annual average TPS contents of eight species of Indocalamus increased significantly compared to those under the CK treatment, with Jin, Dec, and Hir showing a lesser degree of decrease and only Kun, Bas, and Hun exhibiting significant decreases.…”
Section: Response Of Active Substances In the Leaves Of Indocalamus T...mentioning
confidence: 99%
“…This study found similar results: the TPC contents of 14 species of Indocalamus in different seasons ranged between 1.27 mg•g −1 and 5.41 mg•g −1 . Ntobela [54] demonstrated that low-light environments induced an increase in the contents of volatiles and phenolics, and Formisano [55] found that a low-light environment can promote the accumulation of total phenolic compounds. In this study, after the ST treatment, the annual average TPS contents of eight species of Indocalamus increased significantly compared to those under the CK treatment, with Jin, Dec, and Hir showing a lesser degree of decrease and only Kun, Bas, and Hun exhibiting significant decreases.…”
Section: Response Of Active Substances In the Leaves Of Indocalamus T...mentioning
confidence: 99%
“…Some plant-based compounds have cosmetics and nutritional uses; they produce drugs, dyes, fragrances, and dietary supplements [ 18 ]. Plant pathogens and predatory insects have been successfully controlled using plant extracts with high bioactive secondary metabolite contents [ 19 , 20 , 21 ]. Therefore, developing cultivation protocols to optimize the secondary metabolite content, and thus, the medicinal value of plants, is certainly a worthy research venture.…”
Section: Introductionmentioning
confidence: 99%